Assessment of groundwater quality in Sabha area – Libya - Abdulhadi, Elhadi Ramadan Ali; Azahan Awang; Rosmiza Mohd Zainol (Penerbit Universiti Kebangsaan Malaysia, 2021)
Introduction: The groundwater quality in Sabha in Libya is not measured. Also, its impact on human lives and the environment is not being assessed. Objectives: Therefore, this study aims to assess the groundwater quality and its suitability for drinking at five places of Sabha state in Libya, including Sabha city, Samno, Tamnhent, Elzegen, and Godwa. The main aim is to assess 13 parameters of groundwater quality. Methods: From five places, groundwater samples were collected in safe containers and sent to the laboratories. Results: From November 2018 to March 2019, the water samples temperatures averaged were 18.1°C, pH values most of water samples are acidic, except for the Azzighan, which were alkaline, and it ranged from 6.4 to 7.2. In Azzighan, Samno and Sabha, the values of (TDS) and (Ec) exceeded far higher than the desirable limits. The Chloride (Cl) values ranged between 36.7 to 396.8 mg/L, and it was higher than the permissible limit in Azzighan, Tamanhint and Sabha. As for the Nitrate (No3) of well waters were within the desirable limits, except Sabha and Ghadduwah, which were high. high levels of (So4) and (Fe)were found in Azzighan and Samno, the values of (Mg++) recorded in the well waters were not of any concerned were within the prescribed limits. High levels of (So4) were found in Azzighan and Samno, reaching 2230 and 2419 Straight As the normal range does not exceed 150 mg/L Libyan standard. The most spread and comparatively higher E. coli counts in the Sabha well here it arrived 36 cm3. Discussion: The water quality index (WQI) revealed of well waters of study area as follows, the well waters of Tamanhint (WQI: 93.61) and Ghadduwah (WQI:83.76) They were slightly polluted (Class B), were good to drinking. Except (Cl) in Tamanhint and (K) in Ghadduwah all other parameters studied in these two places were well within their standard desirable limits. Moderately polluted well waters (Class C) were located in Azzighan (WQI: 61.06), they require suitable treatments. The well water of Samno (WQI: 45.77) (class D) however, was excessively polluted and Sabha (WQI: 38.86) Severely polluted (class E) and was not potable.Suitable suggestions were made to improve the quality of groundwater of SW Libya.